Ministry of Finance Regulation No.48/2023: How Are Gold Jewelry Dealers Taxpayers’ Awareness? - Hartanto, Susanna (E-Jurnal Akuntansi, 2024)
This study aimed to determine gold jewelry dealers’ taxpayers' awareness of Ministry of Finance Regulation No 48 Year 2023. The novelty of this research is the coverage of the new comprehensive tax regulation from upstream to downstream in gold jewelry industry. It will rise the potency of tax revenue from this industry, but at the same time we have to know about gold jewelry dealers’ taxpayers' awareness for this new regulation because it will affect the taxpayers’ compliance. This is a new regulation including Income Tax Article 22 and Value Added Tax for gold jewelry dealers’ taxpayers. A lot of gold jewelry dealers’ taxpayers weren’t aware of the new rule and even, some of them still didn’t apply the previous regulations. Data was collected through questionnaires and interviews. Qualitative descriptive analysis was used to analyze the awareness of gold jewelry dealers’ taxpayers. The results of this study indicate that the awareness of gold jewelry dealers’ taxpayers is still low for the new regulation. The implementation of Ministry of Finance Reg No 48 Year 2023 will need further socialization to have a positive and significant effect on taxpayer compliance. Keywords: Gold jewelry dealers; Income Tax, Value Added Tax; Ministry of Finance Regulation No 48 Year 2023